Assessment of the Soil Seed Bank Aiming at Transposition to Forest Regeneration in the Western Amazonia - Araújo, Bruno Machado; Alves, Anatércia Ferreira; Melo, Paulo Alexandre Fernandes Rodriques de; Santos, Leonardo Hunaldo dos; Mesquita, Mário Luiz Ribeiro (Journal of Agricultural Studies, 2021)
This study evaluated the soil seed bank’s germination potential and density in five distinct environmental areas namely: a) regenerated forest, b) secondary forest, c) degraded pasture, d) Eucalyptus sp. plantation and e) fallow corn growing area, with a view to regenerate forests in Western Amazonia using tray germination methodology. We assessed floristic similarity and diversity using the Jaccard Similarity Index and the Shannon Diversity Index, respectively. We computed each species’ phytosociological parameters: density, frequency and importance value of each species. We recorded a total 3674 individuals from 51 species and 21 families. The families with the highest species richness were Asteraceae, Malvaceae, Cyperaceae and Poaceae that contributed to 43% of the total species observed. The most important species computed in the phytosociological analysis were Chamaesyce hirta, Corchorus aestuans, Cyperus iria and Chamaesyce prostrata. All species had a herbaceous life form, which in the literature, are considered weeds. We documented the largest number of individuals in the fallow corn growing area that had 3620 plants m-2 and the smallest number in the regenerated forest that had 183 plants m-2. We observed the greatest floristic similarity between the secondary forest and Eucalyptus sp. plantation (40%), and the greatest floristic diversity in the Eucalyptus sp. plantation (H '= 2.59 nats individual-1). In conclusion, the transposition of the soil seed bank is not recommended for forest regeneration and recovery in degraded areas due to massive weed predominance in the soil seed bank.